A Netnography Approach to Understanding Gimmicks in Oke Gas Jingle in TikTok Rhetoric - Taufiq (Vol. 3 No. 1 (2025): Proceeding of International Conference on Cultures & Languages 2025)
This research looks at how political campaigns use fun and catchy content on social media, particularly on TikTok. It focuses on the viral jingle “Oke Gas” used by Prabowo Subianto and Gibran Rakabuming during Indonesia’s 2024 presidential election. As more people use the internet and social media, political campaigns have also changed. They now use videos, songs, and dances to attract voters, especially young people. One example is how the “Oke Gas” jingle became popular and was used to promote the number 02 candidates in a fun and modern way. To understand this, this research uses Sianne Ngai’s idea of the gimmick. A gimmick is something that looks fun and exciting but may not have much real value. This theory helps explain why some campaign content feels entertaining but later seems empty or disappointing. This research uses a qualitative method called netnography, which studies online behavior. Four TikTok videos with the “Oke Gas” jingle and the comments were analyzed, both before and after the election. At first, many people liked the jingle and shared positive comments. But after the candidates won and introduced some unpopular policies, public opinion changed. People started making fun of the jingle and felt disappointed. The results show that fun campaign tools like jingles can get attention fast, but they may lose meaning over time if not followed by good leadership. This research helps to understand how political messages are shared online and suggests that future campaigns should focus not only on being entertaining but also on being honest and meaningful.